MEMBERANTAS TINDAK PIDANA KORUPSI DI INDONESIA DENGAN MENATA BIROKRASI DALAM KERANGKA GOOD GOVERNANCE - SJAHRUDDIN RASUL (Jurnal Media Hukum, 2012)
Considering the severe corruption in Indonesia, its eradication then could not be conducted partially. It needs a holistic eradication corruption which involves the whole aspect, including Indonesian people and government institutions. Particularly from the side of government institution, it needs harder effort, related with the existence of bureaucracy obstacle and a poor good governance system inside the government organization. inline with that, one of the strategy that has to be used is to manage bureaucracy in accordance with the principle of good governance. Good governance consists of three principles. i.e: transparancy, participative and accountability. in addition to implement the good governance principle, job assesment on the bureaucracy has to be implemented